2022
DOI: 10.3390/ijerph192316068
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronotype on Risk-Taking Behavior: The Chain Mediation Role of Self-Control and Emotional Stability

Abstract: Background: Although previous studies indicate that chronotype might be associated with risk-taking behavior, the specific mechanism has not been thoroughly discussed. This study aimed to fill this gap by exploring the mediating role of self-control and the chain mediating role of self-control and emotional stability between chronotype and risk-taking behavior. Methods: A total of 547 Chinese college students between 18 and 24 years old were selected to complete the Morningness–Eveningness Questionnaire (MEQ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It is also a painful emotion and as with most responses to pain, negative emotions increase, including anxiety, sadness, and anger, while positive emotions decrease ( Williams, 2007 ). When individuals are excluded, they feel alienated, helpless, and self-denial, causing dysfunctional cognitive-emotional abilities, which manifests more problem behaviors ( Reiter-Scheidl et al, 2018 ; Zhang et al, 2022 ). A study on Chinese college students showed that experiencing ostracism depletes college students’ self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a painful emotion and as with most responses to pain, negative emotions increase, including anxiety, sadness, and anger, while positive emotions decrease ( Williams, 2007 ). When individuals are excluded, they feel alienated, helpless, and self-denial, causing dysfunctional cognitive-emotional abilities, which manifests more problem behaviors ( Reiter-Scheidl et al, 2018 ; Zhang et al, 2022 ). A study on Chinese college students showed that experiencing ostracism depletes college students’ self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a significant relationship between eveningness and low self-control [18,19]. Related to this relationship, risk-taking behavior is likely associated with M-E preference, with evening types reporting higher levels of risk-taking [20][21][22]. Furthermore, several studies have indicated that emotional variables correlate with M-E preference [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%